Financialization The Economics of Finance Capital Domination - Palley, T. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The term financialization is a term that has become popular to describe developments within the global economy, and particularly within developed industrialized economies, over the past thirty years. The book is divided into four sections, which together give a comprehensive treatment of the economics and political economy of financialization.